Transcatheter Structural Heart Disease Interventions Clinical Update - Taramasso, Maurizio; Tagliari, Ana Paula (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This reprint focuses on the transcatheter treatment of the main structural heart diseases covering the latest innovations and hot topics on this subject. All the technological developments witnessed in recent decades have made structural heart disease interventions a growing field and have contributed to offering patients less invasive, more effective, and safe alternative approaches.